2020
DOI: 10.1016/j.breast.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Winter is over: The use of Artificial Intelligence to individualise radiation therapy for breast cancer

Abstract: Artificial intelligence demonstrated its value for automated contouring of organs at risk and target volumes as well as for auto-planning of radiation dose distributions in terms of saving time, increasing consistency, and improving dose-volumes parameters. Future developments include incorporating dose/outcome data to optimise dose distributions with optimal coverage of the high-risk areas, while at the same time limiting doses to low-risk areas. An infinite gradient of volumes and doses to deliver spatially-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 88 publications
(116 reference statements)
0
18
0
Order By: Relevance
“…31,[103][104][105] The ultimate aim is to achieve individualised, risk-adapted radiotherapy, combining a variety of biomarkers with novel applications of artificial intelligence. [106][107][108] Early breast cancer: systemic therapy…”
Section: Early Breast Cancer: Locoregional Therapymentioning
confidence: 99%
“…31,[103][104][105] The ultimate aim is to achieve individualised, risk-adapted radiotherapy, combining a variety of biomarkers with novel applications of artificial intelligence. [106][107][108] Early breast cancer: systemic therapy…”
Section: Early Breast Cancer: Locoregional Therapymentioning
confidence: 99%
“…Deep learning-based auto-segmentation has been widely investigated in head & neck, lung, and prostate cancers and has demonstrated clinically relevant impact with regard to saving time and mitigating inter-observer variability [23,24,34]. Although several studies have reported the feasibility of the deep learning-based approach for the breast, training and testing has only been performed for ipsilateral breast CTVs [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…An early diagnosis of breast cancer and appropriate risk analysis are crucial for the treatment of this disease and there are new studies reporting the use of big data and AI to achieve an earlier diagnosis of breast cancer (9). In the multidisciplinary treatment of breast cancer, in addition to experience-based medicine, AI technologies are now being developed in the fi elds of surgery, oncology and radiation oncology, to offer the patients the opportunities for personalized treatment (4,10,11).…”
Section: Introductionmentioning
confidence: 99%